Peran Orang Tua dalam Membentuk Karakter Disiplin dan Tanggung Jawab Anak Usia Sekolah Dasar melalui Pendidikan Agama - Dwi Siska; Babyta Priyanka Aishwarya Bana; Dian Rif’iyati (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This study looks at how important it is for parents to use religious education to teach their kids discipline and responsibility. The study, which is based on a review of the literature, emphasizes how these character qualities are successfully fostered when religious principles are consistently used in day-to-day activities and are backed by parental role models. Results show that religious education builds a strong basis for discipline and accountability in addition to enhancing children's spirituality. It is advised that future research use interviews or direct observation to better understand these activities in authentic contexts. In order to naturally instill the principles of discipline and responsibility in their children, parents are urged to use technology, embrace creative thinking, and establish nurturing surroundings at home.